2017
DOI: 10.18632/oncotarget.15461
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor receptor 2/AKT and ERK signaling pathways contribute to the switch from fibroblasts to CAFs by progranulin in microenvironment of colorectal cancer

Abstract: Cancer associated fibroblasts (CAFs) are a crucial cellular component in tumor microenvironment and could promote tumor progression. CAFs are usually derived from resident fibroblasts, which undergoing an activated process stimulated by tumor cells. However, the agents and mechanism driving this switch have not yet been elucidated. Progranulin (PGRN), a well acknowledged secreted glycoprotein, could promote proliferation and angiogenesis of colorectal cancer (CRC) cells, and high expression of PGRN correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…In addition, analysis of the signaling events downstream of TNF showed that TNF-canonical signaling in Tnf ΔARE/+ ;Tnfrsf1b MCKO SFs were comparable with WT control, since JNK and ERK kinases displayed similar phosphorylation kinetics and nuclear factor of κ light polypeptide gene enhancer in B cells inhibitor, α (Nfkbi) showed physiological degradation ( Figure 6H and Supplemental Figure 9, A-C). In contrast, Akt kinase, which belongs to the noncanonical TNF signaling pathway and is associated with positive regulation of cell proliferation and cancer, fails to become phosphorylated, pointing to another level of Tnfr2-mediated cell proliferation regulation downstream of TNF that associates with the PI3K-Akt signaling pathway ( Figure 6I and Supplemental Figure 9D), similar to what has been observed in cancer cells (54,55).…”
Section: Resultssupporting
confidence: 70%
“…In addition, analysis of the signaling events downstream of TNF showed that TNF-canonical signaling in Tnf ΔARE/+ ;Tnfrsf1b MCKO SFs were comparable with WT control, since JNK and ERK kinases displayed similar phosphorylation kinetics and nuclear factor of κ light polypeptide gene enhancer in B cells inhibitor, α (Nfkbi) showed physiological degradation ( Figure 6H and Supplemental Figure 9, A-C). In contrast, Akt kinase, which belongs to the noncanonical TNF signaling pathway and is associated with positive regulation of cell proliferation and cancer, fails to become phosphorylated, pointing to another level of Tnfr2-mediated cell proliferation regulation downstream of TNF that associates with the PI3K-Akt signaling pathway ( Figure 6I and Supplemental Figure 9D), similar to what has been observed in cancer cells (54,55).…”
Section: Resultssupporting
confidence: 70%
“…Such a cell density/receptor number dependency of the ability of PGRN to interfere with TNF binding is again not straightforwardly compatible with competitive binding inhibition. Third, PGRN enhances TNF-induced TNFR2-mediated proliferation and suppressive activity of regulatory T cells ( 9 ) and PGRN-induced Akt signaling has found to be inhibited by neutralizing TNFR2 antibodies ( 15 , 18 ). Both observations again argue against competitive inhibition of TNF binding by PGRN.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, activating TNFR2 on tumor-promoting cell types, such as fibroblasts might limit tumor cell invasion and metastasis and improve tumor therapy ( 97 100 ).…”
Section: Targeting Tnfr2 For Tumor Therapymentioning
confidence: 99%